Improved recovery of bacteriophage M13 using an ATPS‐based bioprocess. (6th August 2018) - González‐Mora, Alejandro; Ruiz‐Ruiz, Federico; Benavides, Jorge; Rito‐Palomares, Marco
Abstract : Aqueous two‐phase systems (ATPS) have been widely exploited for the recovery and partial purification of biological compounds. Recently our research group characterized the primary recovery and partial purification of bacteriophage M13 using polymer‐salt and ionic liquid‐salt ATPS. From such study, it was concluded that PEG 400‐potassium phosphate ATPS with a volume ratio ( V R ) of 1 and 25% w/w TLL were the best suitable for the primary recovery of bacteriophage M13 from a crude extract, achieving a recovery yield of 83.3%. Although such system parameters were proven to be adequate for the recovery of the product of interest, it was concluded that further optimization was desirable and attainable by studying the effect of additional system parameters such as V R, concentration of neutral salt (M) and sample load (% w/w). This research work presents an optimization of a previously reported process for the recovery of bacteriophage M13 directly from a crude extract using ATPS. The increase in V R and sample load showed a positive effect in the recovery of M13 indicating an improved performance of the proposed ATPS. According to the results presented here, a system composed of PEG 400 17.2% (w/w), potassium phosphate 15.5% (w/w) and a sample load of 30% (w/w) allowed the recovery of M13 directly from a crude extract with a top phase recovery of 80.1%, representing an increase of 4.8 times in the final concentration and a reduction of 2.65 times in the processing costs. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018 © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1177–1184, 2018